PERLUASAN KOTA DALAM REALITAS SOSIAL DAN KULTURAL MASYARAKAT - T. Yoyok Wahyu Subroto (Populasi, 2002)
The expansion of cities is one of the most interesting issues, especially in the backdrop of increasing scarcity of space for the burgeoning population as well as environmental concerns, which among other things, advocate for the preservation of conservation areas on the city’s outskirts. The expansion of cities has resulted into the spatial, social, and cultural transformation of suburban areas. The importance of adopting spatial development pattern for areas on city fringes should foster the formulation of development that should take cognizance of the social and spatial aspects of such areas. Upon implementation, spatial development pattern will facilitate the proper phasing, and direction of the transformation process. Proper urban /city development and expansion should be conducted through five phases, which entail: 1) determining the goal, 2) creating the development and conservation pattern, 3) identifying the area of focus, 4) planning, 5) and implementation. If city development is based on the five phases aforementioned, it should evolve into a controllable expansion pattern, which is known as accretion expansion.